Detection and Molecular Characterization of Human Adenovirus Infections among Hospitalized Children with Acute Diarrhea in Shanghai, China, 2006–2011. (28th December 2017) - Lu, Lijuan; Zhong, Huaqing; Su, Liyun; Cao, Lingfeng; Xu, Menghua; Dong, Niuniu; Xu, Jin
Abstract : Background : Human adenovirus (HAdV) is considered a significant enteropathogen associated with sporadic diarrhea in children. However, limited data are available regarding the epidemiology of HAdV in hospitalized children with viral diarrhea in Shanghai. The aim of this study was to characterize the epidemiology of HAdVs and describe their association with acute diarrhea in hospitalized children. Methods : A total of 674 fecal samples were subjected to PCR or RT-PCR to detect RVA, HuCV, HAstV, and HAdV. Results : HAdV infections were detected in 4.7% (32/674) of specimens, with detection rates of 13.4% (11/82), 4.6% (8/174), 3.2% (4/124), 4.1% (3/74), 2.0% (2/100), and 3.3% (4/120) from 2006 to 2011, respectively. Comprehensive detection of the four viruses revealed the presence of a high percentage (90.6%) of coinfections among HAdV-positive samples, where HAdV+RVA was the most prevalent coinfection. Of the 32 HAdV-positive samples, 50.0% (16/32) were classified as HAdV-41, and 18.8% (6/32) were classified as HAdV-3. Almost 94.0% of children infected with HAdV were less than 24 months of age. Conclusions : These results clearly indicated diversity across the HAdV genotypes detected in inpatient children with acute diarrhea in Shanghai and suggested that HAdVs play a role in children with acute diarrhea.